Design and Development Optimized FIFO Queue System for Food Outlets - Tanusaputra, Johan William; Budhi, Robby Kurniawan; Trisno, Indra Budi (Jurusan Teknologi Informasi Universitas Semarang, 2025)
In today's fast-paced food service industry, the efficiency of queue management is vital to operational success, profitability, and customer satisfaction. This study evaluates an integrated queue management system's impact on these critical areas. The results show an average satisfaction score of 80.11% from customers and 90.37% from food outlet owners, demonstrating the system's strong effectiveness. The research focused on the importance of reducing perceived waiting times through real-time updates, which enhance customer tolerance and satisfaction. By combining online and onsite ordering, the system provides real-time updates, order tracking, and notifications to boost efficiency and minimize cancellations. Despite some identified weaknesses, such as the absence of direct customer reviews and existing bugs, the system holds significant potential for improving user experience. These findings highlight the necessity for continuous development and maintenance to optimize the system further. Overall, this approach promises to advance the operational capabilities and customer satisfaction levels of food outlets.